Water supply in Malaysia. - Yong, Eu Fan (1989)
Since the United Nations declaration of the 1980's as the International Drinking Water Supply and Sanitation Decade, the Malaysian Government had undertaken a national water-resources study and drawn-up priority action plans. This has resulted in accelerated expenditure on water and sanitation and the setting up of projects for funding, design and implementation. It was noticeable that since 1981 water conservation and the provision of piped water especially to the rural population has become a major government concern, and consumes a large proportion of the annual budgets. Plans are under way to privatise water resources management and development to help ease the heavy financial burden on the Government. This paper reviews the water resources situation, the major water supply projects, the institutional framework and financing system for water resources development.